2005
DOI: 10.1242/jcs.02379
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1: a key regulator of adhesion and migration

Abstract: The dynamic rearrangement of cell-cell adhesion is one of the major physiological events in tissue development and tumor metastasis. Polarized cell migration, another key event, is a tightly regulated process that occurs during tissue development, chemotaxis and wound healing. Rho-family small GTPases, especially Rac1 and Cdc42, play pivotal roles in these processes through one of their effectors, IQGAP1. Recent studies reveal that IQGAP1 regulates cadherin-mediated cell-cell adhesion both positively and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
329
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(348 citation statements)
references
References 78 publications
12
329
0
7
Order By: Relevance
“…Of the many putative proteins identified (Table S1), two candidates, IQGAP1 and IQGAP3, were particularly notable for their pleiotropic roles in signal transduction (35,36). The three highly homologous IQGAPs (IQGAP1-3) contain multiple domains that bind to and modulate the activity of a plethora of signaling molecules, including Rho GTPases, MAP kinase (MAPK), and components of Wnt pathway E-cadherin, β-catenin, and adenomatous polyposis coli (35,36). We first confirmed that full-length LGR4 interacts with IQGAP1 as well as with IQGAP2 and IQGAP3 by co-IP analysis ( Fig.…”
Section: Rspo-mentioning
confidence: 99%
See 2 more Smart Citations
“…Of the many putative proteins identified (Table S1), two candidates, IQGAP1 and IQGAP3, were particularly notable for their pleiotropic roles in signal transduction (35,36). The three highly homologous IQGAPs (IQGAP1-3) contain multiple domains that bind to and modulate the activity of a plethora of signaling molecules, including Rho GTPases, MAP kinase (MAPK), and components of Wnt pathway E-cadherin, β-catenin, and adenomatous polyposis coli (35,36). We first confirmed that full-length LGR4 interacts with IQGAP1 as well as with IQGAP2 and IQGAP3 by co-IP analysis ( Fig.…”
Section: Rspo-mentioning
confidence: 99%
“…IQGAPs contain several domains that bind to distinct signaling and structural proteins (35,36). To map the IQGAP1 domain responsible for interacting with LGR4, a series of IQGAP1 truncation and deletion mutants were constructed (Fig.…”
Section: Rspo-mentioning
confidence: 99%
See 1 more Smart Citation
“…IQGAP1 has been reported to interact with βArr2, a scaffold protein that binds to activated GPCRs and regulates signaling and receptor endocytosis (20). IQGAP1 promotes proliferation and migration, and overexpression has been associated with poor prog-nosis in advanced colorectal cancer (21)(22)(23). Interestingly, IQGAP1 can coordinate cell growth and division in a phosphorylation-dependent manner (24).…”
Section: Gpr161 Induces Migration and Invasion Of Mammary Epithelial mentioning
confidence: 99%
“…27 CLIP1 also interacts with IQGAP1 (IQ Motif Containing GTPase Activating Protein 1), which together with CLIP1, is part of a complex that has a role in linking the actin cytoskeleton to MTs during cell migration. 28 In rat neurons, CLIP1 together with IQGAP1 controls dendrite morphology, again possibly by regulating the interaction between MTs and the actin cytoskeleton. 9 The second zinc knuckle in the C-terminal domain of CLIP1 takes part in direct interaction with the dynactin subunit 1, DCTN1 (P150 Glued ) of the dynein/dynactin complex.…”
Section: Discussionmentioning
confidence: 99%